The role of different P-glycoproteins in hepatobiliary secretion of fluorescently labeled short-chain phospholipids - Charles M.G. Frijters; Coosje J. Tuijn; Roelof Ottenhoff; Bart N. Zegers; Albert K. Groen; Ronald P. J. Oude Elferink (Journal of Lipid Research, 1999)
Class III P-glycoproteins (Pgps) mediate biliary phosphatidylcholine (PC) secretion. Recent findings that class I P-glycoproteins are able to transport several short-chain phospholipid analogues raises questions about the role of these Pgps in physiological lipid transport. We investigated the biliary secretion of C6-7-nitro-2,1,3-benzoxadiazol-4-yl (NBD)-labeled ceramide and its metabolites in Mdr1a/b and Mdr2 knockout mice compared to control mice. Biliary secretion of these NBD-lipids was unaffected in Mdr1a/b –/– mice. Thus neither Mdr1a nor Mdr1b Pgp mediates biliary secretion of these lipids. In contrast, secretion of all three NBD-labeled short-chain phospholipids was significantly reduced in Mdr2 –/– mice. As in vitro studies revealed that Mdr2 Pgp is not able to translocate these lipid analogues, we hypothesized that Mdr2 –/– mice had a reduced PC content of the exoplasmic canalicular membrane leaflet so that extraction of the short-chain lipid probes from this membrane by canalicular bile salts was impaired. To investigate this possibility we studied the bile salt-mediated extraction of natural sphingomyelin (SM) and NBD-labeled short-chain SM from small unilamellar vesicles of different lipid composition. Natural SM could be extracted by the bile salt tauroursodeoxycholate from vesicles containing PC, cholesterol (CHOL), and SM (1:2:2) but not from vesicles containing only SM and CHOL (3:2). NBD-labeled short-chain SM could be extracted from vesicles containing PC while its extraction from pure SM:CHOL vesicles was reduced by 65%. These data confirm that the efficiency of NBD-SM extraction depends on the lipid composition and suggest that the canalicular membrane outer leaflet of Mdr2 –/– mice has a reduced PC content.—Frijters, C. M. G., C. J. Tuijn, R. Ottenhoff, B. N. Zegers, A. K. Groen, and R. P. J. Oude Elferink. Role of different P-glycoproteins in hepatobiliary secretion of fluorescently labeled short-chain phospholipids. J. Lipid Res. 1999. 40: 1950–1957.